Cost-effectiveness of hypofractionated versus conventional radiotherapy in patients with intermediate-risk prostate cancer: An ancillary study of the PROstate fractionated irradiation trial – PROFIT. (August 2022) - Zhou, K.; Renouf, M.; Perrocheau, G.; Magné, N.; Latorzeff, I.; Pommier, P.; Créhange, G.; Paumier, A.; Bera, G.; Martin, J.; Catton, C.; Bellanger, M.; et al.
Highlights: This is the first European cost-effectiveness analysis of moderately hypofractionated radiotherapy (H-RT) compared to conventional radiotherapy (C-RT). Using H-RT as a standard treatment for intermediate-risk prostate cancer is cost saving. The economic evidence supporting the shift towards H-RT in France should stimulate reimbursement policy changes. Abstract: Purpose: To evaluate the cost-effectiveness of moderate Hypofractionated Radiotherapy (H-RT) compared to Conventional Radiotherapy (C-RT) for intermediate-risk prostate caner (PCa). Methods: A prospective randomized clinical trial including 222 patients from six French cancer centers was conducted as an ancillary study of the international PROstate Fractionated Irradiation Trial (PROFIT). We carried-out a cost-effectiveness analysis (CEA) from the payer's perspective, with a time horizon of 48 months. Patients assigned to the H-RT arm received 6000 cGy in 20 fractions over 4 weeks, or 7800 cGy in 39 fractions over 7 to 8 weeks in the C-RT arm. Patients completed quality of life (QoL) questionnaire: Expanded Prostate Cancer Index Composite (EPIC) at baseline, 24 and 48 months, which were mapped to obtain a EuroQol five-dimensional questionnaire (EQ-5D) equivalent to generate Quality Adjusted Life Years (QALY). We assessed differences in QALYs and costs between the two arms with Generalized Linear Models (GLMs). Costs, estimated in euro (€) 2020, were combined with QALYs to estimate the Incremental Cost-effectiveness ratio (ICER) with non-parametric bootstrap. Results: Total costs per patien were lower in the H-RT arm compared to the C-RT arm €3, 062 (95 % CI: 2, 368 to 3, 754) versus €4, 285 (95 % CI: 3, 355 to 5, 215), (p < 0.05). QALY were marginally higher in the H-RT arm, however this difference was not significant: 0.044 (95 % CI: − 0.016 to 0.099). Conclusions: Treating localized prostate cancer with moderate H-RT could reduce national health insurance spending. Adopting such a treatment with an updated reimbursement tariff would result in improving resource allocation in RT management.